The Influence Of Prices, Baristas, Products, And Store Atmosphere On Sustainability Coffee Shop Business In The Lowlands - Dhifa Meita Jihan Nabilah; Putri Anggini Ryandi; Riyan Frediansyah; Wachdijono Wachdijono (Al-Makki Publisher, 2023)
Business sustainability in the lowlands is the ability to continue to adapt to changing consumer trends and preferences. Therefore, these business actors must conduct research related to the sustainability of the business. This research aims to determine the influence of prices, baristas, products, and atmosphere on the sustainability of coffee shop businesses in the lowlands. The study was conducted in Tangerang City, a lowland area with many modern coffee shops. The research time is from July to September 2023. The research design used is quantitative and survey methods. The research population is coffee shop consumers in Tangerang City, whose number is unknown, so the sample size was determined deliberately, namely 100 consumers. Data analysis uses the Structural Equation Modeling instrument. The research results show that the price and product variables positively affect coffee shop businesses' sustainability in Tangerang City's lowlands. Still, the barista variables and shop atmosphere have no effect. The indicator that best explains the condition of the price variable is